British film directors : a critical guide - Shail, Robert (Edinburgh University Press, 2007)
British national cinema has produced an exceptional track record of innovative, creative and internationally recognised filmmakers, amongst them Alfred Hitchcock, Michael Powell and David Lean. This tradition continues today with the work of directors as diverse as Neil Jordan, Stephen Frears, Mike Leigh and Ken Loach. This concise, authoritative volume analyses critically the work of 100 British directors, from the innovators of the silent period to contemporary auteurs. An introduction places the individual entries in context and examines the role and status of the director within British film production. Balancing academic rigour with accessibility, British Film Directors provides an indispensable reference source for film students at all levels, as well as for the general cinema enthusiast. Key Features A complete list of each director's British feature films. Suggested further reading on each filmmaker. A comprehensive career overview, including biographical information and an assessment of the director's current critical standing. 10 B & W illustrations.
Keywords: Motion picture producers and directors -- Great Britain -- Biography -- Dictionaries.; Producteurs et réalisateurs de cinéma -- Grande-Bretagne -- Biographies -- Dictionnaires anglais.; PERFORMING ARTS -- Film & Video -- Direction & Production.; BIOGRAPHY & AUTOBIOGRAPHY -- Entertainment & Performing Arts.; PERFORMING ARTS -- Film & Video -- Reference.; Motion picture producers and directors; Great Britain; Filmregisseur; Regisseur; Großbritannien; Electronic books.; dictionaries.; Biographies; Dictionaries; Dictionaries.; Dictionnaires.